Case Report: Posterior reversible encephalopathy syndrome after lenvatinib treatment for hepatocellular carcinoma - Chen, Minchun; Shen, Jing; Jia, Rongrong; Chang, Mingze; Zhang, Jingyi; Zheng, Jie; Xue, Runqing; Guo, Lulu; Yan, Kangkang (Frontiers in Pharmacology, 2025)
BackgroundPosterior reversible encephalopathy syndrome (PRES) is characterized by headaches, vision loss, confusion, encephalopathy, seizures, and reversible focal edema on neuroimaging. Early recognition and treatment of PRES are essential to prevent severe complications. Lenvatinib is a multi-targeted kinase inhibitor that is used as a first-line treatment for patients with hepatocellular carcinoma (HCC). Lenvatinib-induced PRES is a less commonly recognized side effect.Case presentationA 72-year-old female patient with HCC, who had no history of hypertension, received lenvatinib therapy. The patient exhibited symptoms such as confusion, altered mental status, headaches, and severe hypertension during treatment. Neuroimaging revealed characteristic findings of vasogenic edema in the white matter of the brain. The patient’s neurological symptoms gradually improved after lenvatinib discontinuation, and follow-up imaging showed a reduction in the white matter abnormalities.ConclusionThe underlying mechanisms of PRES induced by lenvatinib remain unclear, but hypertension is considered a crucial factor in its pathogenesis. This case report adds to the understanding of the potential adverse effects associated with lenvatinib in patients with HCC, emphasizing the need for vigilance in monitoring and managing such complications to ensure the safety and wellbeing of patients undergoing this treatment.